Influence of HF2- geometry on magnetic interactions elucidated from polymorphs of the metal-organic framework [Ni(HF2)(pyz)2]PF6 (pyz = pyrazine). - Manson, J; Carreiro, K; Lapidus, S; Stephens, P; Goddard, P; Del Sesto, R; Bendix, J; Ghannadzadeh, S; Franke, I; Singleton, J; Lancaster, T; Möller, J; et al. (2012)
A tetragonal polymorph of [Ni(HF(2))(pyz)(2)]PF(6) (designated β) is isomorphic to its SbF(6)-congener at 295 K and features linear Ni-FHF-Ni pillars. Enhancements in the spin exchange (J(FHF) = 7.7 K), Néel temperature (T(N) = 7 K), and critical field (B(c) = 24 T) were found relative to monoclinic α-PF(6). DFT reveals that the HF(2)(-) bridges are significantly better mediators of magnetic exchange than pyz (J(pyz)), where J(FHF) ≈ 3J(pyz), thus leading to quasi-1D behavior. Spin density resides on all atoms of the HF(2)(-) bridge whereas N-donor atoms of the pyz ring bear most of the density.